Fluidization Characteristics of Medium-High-Consistency Pulp Fiber Suspensions with an Impeller - Ye Daoxing; Li Hong (International Journal of Rotating Machinery)
When the mass concentration exceeds 7%, pulp suspensions stop flowing and act like a solid. To investigate the fluidization characteristics of medium-high-consistency pulp suspensions and achieve pulp fluidization and pumping, experiments were carried out with waste tissue pulp and unbleached kraft pulp. The objectives of this paper were to study the rheology of medium-high-consistency pulp and to determine accurate parameters for the physical Herschel-Bulkley model. To validate this model, computational fluid dynamics (CFD) results were compared to experimental data. The simulation values were very similar and were in agreement with experimental results.